HUBUNGAN PENGETAHUAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF USIA > 6-12 BULAN DI KECAMATAN TALANGO KABUPATEN SUMENEP - Sri Sumarni; Nelyta Oktavianisya (Wiraraja Medika : Jurnal Kesehatan, 2017)
The first and main food for babies is breast milk (ASI). Breast milk contains the most completenutritional composition and ideal for the growth and development of infants during the first 6months. The percentage of coverage of exclusive breastfeeding in Sumenep in 2011-2013decreased but increased in 2014 (45.5%) but has yet to reach the target (80%). Coverage rate ofexclusive breastfeeding in the District Talango any decline of the Year The year 2012-2014 is stillfar from the target attainment (80%). This study aims to determine the relationship betweenknowledge of mothers exclusively breastfeeding infants aged> 6-12 months.This research is analytic survey with cross sectional approach. The number of samples in thisstudy were as many as 38 nursing mothers who have infants aged> 6-12 months in the workingarea of Puskesmas (Health Center) Talango sub-district Talango taken using proportionate randomsampling technique. Collecting data through interviews using a questionnaire. The statistical testused to analyze the relationship between variables using chi square.The results showed that most respondents (55.3%) had good knowledge and 60.5% ofrespondents who breastfed exclusively. The results of data analysis showed a significantrelationship between knowledge and exclusive breastfeeding (p = 0.028).Efforts to improve the implementation of exclusive breastfeeding for infants aged> 6-12months through empowerment to health workers, such as by an increase in personnel and skills inorder to increase the use of breast milk.